BUMDes School For Financial Management - Haryanto; imawan, amrizal; majid, abdul (CV. Inara, 2022)
For BUMDes (village-owned enterprise) managers, orderly financial records and reports are crucial matters to know the financial position of their business. Systematic financial record is a tool for making decisions regarding business development plans, as well as requirements for applying for capital or getting investors. The administrative system for recording BUMDes financial reports is mostly still manual which seems complicated and lengthy, so there are still many BUMDes managers who do not have financial reports in running their business. The purpose of this community service was to increase understanding and competence regarding accounting literacy for BUMDes managers. These community service partners were directors and treasurers of 27 BUMDes in Paciran and Karanggeneng districts. Community service activities were carried out through training and mentoring methods and attended by the BUMDes managers and treasurers. The training was conceptualized in the form of lectures, discussions, and practice of preparing financial statements. The results of this service indicated that there was an increase in the knowledge and skills of BUMDes managers regarding administration, rules, utilization of village asset,and financial bookkeeping. The output of science and technology achieved was practical knowledge of simple accounting, namely the preparation of financial reports in accordance with existing standards and regulations.